Versatile 3D porous recycled carbon garments with fully-loaded active materials in the current collector for advanced lithium-ion batteries - Cho, Hyunjin; Kim, Yeonho; Yun, Yong Ju; Lee, Kyu Seung; Shim, Jaeho; Lee, Chil-Hyoung; Seo, Jin Won; Hong, Won G.; Kim, Hae Jin; Kim, Hak Yong; Son, Dong Ick (ELSEVIER SCI LTD, 2019)
We have developed a new and versatile three-dimensional (3D) porous and the conductive carbon spun fabric (CSF) structure and applied it to the current collector for advanced lithium-ion batteries (LIBs). The 3D porous CSF are manufactured from recycled oxidized polyacrylonitrile (Oxi-PAN) staple fibers via the spinning, the knitting, stabilization, and carbonization process in order. Furthermore, we have demonstrated the conductive Tshirts and gloves and investigated the structural, electrical, mechanical, and thermal properties of the CSF through various analytical methods including Joule heating simulation as well as the deformation simulation. The CSF with its 3D porous structure is applied as a current collector for advanced lithium batteries in order to replace the conventionally used metal-based current collector. During battery performances, the porous 3D network structure of the CSF provides effective diffusion pathway for lithium ions during the charge/discharge processes. Consequently, the CSF shows not only the improved cycling stability than that of the conventional aluminum current collector but also demonstrating high-rate performances at high percentage loading of active materials in the current collector. The pouch-type LIBs with the CSF/LiFePO4 composites electrode exhibits excellent mechanical stability and flexibility with showing a discharge capacity of 148.7 mA h g(-1) at 2 C over 250 cycles over the 1200 times bending with a radius of 12 mm.
Keywords: THERMAL-CONDUCTIVITY; WEARABLE ELECTRONICS; FILM; FABRICATION; GRAPHENE; DESIGN; ANODE; COMPOSITES; CAPACITY; FIBERS